Is perceived neighbourhood physical disorder associated with muscle strength in middle aged and older men and women? Findings from the US health and retirement study. Issue 3 (10th January 2020) - Duchowny, Kate A; Glymour, M Maria; Cawthon, Peggy M
Abstract : Background: Research documenting the relevance of neighbourhoods for the health of older adults has focused on global physical functioning outcomes, such as disability, rather than physiologic impairments that lead to disability. Muscle weakness is an age-related impairment and a central mechanism of disability. Evaluating neighbourhood effects on muscle weakness may offer insight into physiologic mechanisms of disability. We examined the association between perceived neighbourhood disorder and muscle strength in a nationally representative sample of US adults aged 51+. Methods: Among 11 277 participants (57% women; mean age: 66.6 years) in the Health and Retirement Study (2012–2014), we investigated whether self-reported neighbourhood physical disorder (1–7 scale, mean=2.61, SD=1.45); presence of vandalism/graffiti, litter, deserted houses, feeling safe walking alone) was associated with mean hand grip strength using linear regression models with sampling weights. We tested whether the association between neighbourhood disorder and grip strength differed by age and gender. Results: After adjusting for demographic characteristics, marital status, education and household wealth, residence in neighbourhoods with high perceived physical neighbourhood disorder was associated with lower muscle strength for men (β=−1.95 kg; 95% CI, 2.68 to –1.22) and to a lesser extent, for women (β=−0.64 kg, 95% CI, −1.11 to –0.19), (p for interaction <0.0001). For both men and women, associations between neighbourhood physical disorder and grip strength were more adverse among the middle aged (51–64 years) than for older (ages 65+) adults. Discussion: Perceived neighbourhood disorder was associated with lower muscle strength. Future studies should more rigorously evaluate causality and evaluate potential interventions.